2017
DOI: 10.22161/ijeab/2.4.90
|View full text |Cite
|
Sign up to set email alerts
|

Use of Nanotechnology in Food Industry: A review

Abstract: Abstract-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 37 publications
0
10
0
1
Order By: Relevance
“…SNPs produced by self-assembly of supernatants are also a type of resistant starch, and several studies have reported on their digestibility (Liu et al, 2016;2017). Liu et al (2016) compared enzymatic hydrolysis kinetics of native corn starch, cooked corn starch, corn SNCs and corn SNPs.…”
Section: Digestibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…SNPs produced by self-assembly of supernatants are also a type of resistant starch, and several studies have reported on their digestibility (Liu et al, 2016;2017). Liu et al (2016) compared enzymatic hydrolysis kinetics of native corn starch, cooked corn starch, corn SNCs and corn SNPs.…”
Section: Digestibilitymentioning
confidence: 99%
“…Nanoparticles in the food industry are classified according to if they are used as food additives (nano inside) or for food packaging (nano outside) (Samal, 2017). Nano inside is used to improve food quality in terms of shelf-life, texture and flavor.…”
Section: Introductionmentioning
confidence: 99%
“…For example, anticaking agents such as aluminosilicate compounds are often employed in powdered or granulated processed food. In contrast, anatase titanium dioxide is a frequent food brightener and whitener ingredient found in confectionery, sauces, and cheeses ( Table 1 ) ( Samal, 2017 ). SiO2 is primarily used in non-food and food products to thicken pastes, used as an anticaking agent in powdered products to retain flow characteristics, and as a carrier of perfumes or flavours.…”
Section: Nanotechnology In Food Sciencesmentioning
confidence: 99%
“…It provides several opportunities for the development of novel products and the expansion of food system applications including nutraceuticals, functional foods, bioactive substances, and pharmaceuticals, etc. ( Samal, 2017 ). Even more, nanotechnology can be used to detect food pathogens, which are indicators of food quality and safety ( Bott et al, 2014 ).…”
Section: Advanced Technologies To Preserve Processed Colostrum For Human Consumptionmentioning
confidence: 99%